Design of Innovative Non-Routine Learning Strategies in Chemistry Learning - Mujakir, Mujakir; Kurniawati, Yenni; Djamaluddin, Safrijal; Ahmad, Nur Jahan (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2024)
Traditional teaching methods in chemistry have been insufficient in helping students master problem-solving and conceptual understanding across the three levels of chemical representation: macroscopic, submicroscopic, and symbolic. Innovative strategies are needed to address these challenges and improve learning outcomes. This study evaluates the feasibility, practicality, and effectiveness of a non-routine learning strategy as an innovative approach to teaching chemistry. The research adopts the Gall and Gall Research and Development (R&D) model with a 3D design framework (Define, Design, Develop). The study involved chemistry education students from UIN Ar-Raniry Banda Aceh and UIN Sultan Syarif Kasim Riau. Data collection instruments included validation sheets to assess feasibility, observation sheets for practicality and effectiveness, as well as tests and related documents. The findings demonstrate that the non-routine learning strategy is valid, practical, and effective. It significantly enhances students' ability to solve problems and explain chemical concepts using the macroscopic, submicroscopic, and symbolic levels of representation. This non-routine learning strategy represents a feasible and effective innovation in chemistry education, providing a practical tool for improving students’ problem-solving skills and conceptual understanding. Its implementation offers valuable insights for advancing chemistry teaching practices.